Examination of Leg Power and Core Muscle Strength on Linear Kick Velocity in Pencak Silat among Tapak Suci Putera Muhammadiyah 181 Athletes, Majene Regency - Asyhari, Hasbi; Nurliani, Nurliani (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives. In this study, Tapak Suci Putera Muhammadiyah 181 athletes from Majene Regency will demonstrate how leg power and abdominal muscular strength affect the speed of straight kicks during pencak silat. Materials and Methods. Twenty athletes from Tapak Suci Putera Muhammadiyah 181 Majene Regency made up the study's population. Twenty athletes made up the sample size, which was obtained utilizing Saturated Samples. The survey approach was utilized to obtain the data, which included testing and measurements using devices that measured the pencak silat's straight kick speed, leg power, and abdominal muscular strength. Descriptive analysis, product moment correlation analysis, and regression using the normality and linearity precondition tests were all employed in the data analysis methodology. Results. The study's findings show that: 1) Leg power significantly influences the speed of straight kicks in pencak silat among athletes from Tapak Suci Putera Muhammadiyah 181 Majene Regency, with a contribution of 75.3% and a R value of 0.867 and a probability value of 0.000 <0.05. 2) With a R value of 0.646 and a Probability value of 0.002 <0.05, the power of the abdominal muscles significantly contributes 41.8% to the speed of straight kicks in pencak silat among athletes from Tapak Suci Putera Muhammadiyah 181 Majene Regency. 3) With a R value of 0.891 and a Probability value of 0.000 <0.05, the speed of straight kicks in pencak silat among athletes from Tapak Suci Putera Muhammadiyah 181 Majene Regency is significantly influenced by both leg power and abdominal muscle strength at the same time, accounting for 79.3% of the total. Conclusion. The study's findings indicate that, with respective contributions of 75.3% and 41.8%, leg power and abdominal muscular strength significantly influence the speed of straight kicks in pencak silat among Tapak Suci Putera Muhammadiyah 181 participants from Majene Regency. Leg strength and abdominal muscular strength together accounted for 79.3% of the straight kick speed.